Sociocultural Factors Influencing The Use of Modern Contraception in Developing Countries: A Scoping Review - Nur'anisyah, Lisna; Kartini, Farida; Moniz, Maria De Fatima (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2025)
Background: Modern contraception is one of the key strategies in controlling birth rates and improving reproductive health, particularly in developing countries. However, its use still faces various barriers influenced by sociocultural factors. Objective: This study aims to provide an overview of the sociocultural factors influencing the use of modern contraception in developing countries. Methods: This scoping review utilized the PRISMA-ScR checklist, the PCC framework, and the Critical Appraisal assessment. Data were obtained from the PubMed, Wiley Online Library, and the Science Direct databases. Results: A total of 174 relevant articles were identified, but only seven met the inclusion criteria. Key findings included sociocultural factors influencing the use of modern contraception and the effectiveness of its use. Conclusion: This review highlights that sociocultural dynamics, particularly gender norms, religious beliefs, and community perceptions, remain key determinants of modern contraceptive use in developing countries. Strengthening culturally sensitive counseling, engaging male and spiritual leaders, and utilizing digital health platforms are crucial to enhancing uptake and sustaining progress toward universal reproductive health goals.